Bi-Directionality of the Microbiota-Gut-Brain Axis in Patients With Functional Dyspepsia: Relevance of Psychotherapy and Probiotics - Rupp, Sophia Kristina; Stengel, Andreas (Frontiers in Neuroscience, 2022)
Functional dyspepsia is one of the most commonly diagnosed disorders of the gut-brain interaction worldwide. The precise pathogenesis of functional dyspepsia is complex and remains incompletely understood. Therefore, advances in the understanding of functional dyspepsia could change clinical practice. The aim of this review is to highlight the relevance of psychotherapy and probiotics in the context of the microbiota-gut-brain axis in the pathophysiology and especially in the treatment of functional dyspepsia. Therefore, studies which have been conducted to investigate the role of psychotherapy and probiotics in FD and the microbiota-gut-brain axis in the pathophysiology of functional dyspepsia were examined, and the outcomes of this research summarized. There might be a link between changes in the microbiome and functional dyspepsia. Even though, specific alterations in the microbiome that may be pathognomonic in functional dyspepsia remain unclear, the use of probiotics became a viable treatment option for patients with functional dyspepsia. Since mental illness also plays an important role in the pathophysiology of functional dyspepsia, psychotherapy is a useful treatment method, with additional study results indicating that psychotherapy may also shift the microbiome in a favorable direction. Moreover, other findings suggest that probiotics can be used not only to alleviate gastrointestinal symptoms in functional dyspepsia, but also to treat or even prevent mental disorders in these patients. In summary, in this review we highlight the bi-directionality of the microbiota-gut-brain axis in the pathophysiology of functional dyspepsia. Although there are multiple treatment approaches, the burden of disease in patients with functional dyspepsia is still enormous and a definitive therapy to cure this disease does not (yet) exist. Lastly, there is a lack of studies on the impact of dysbiosis, mental health and probiotics on pathophysiology and symptomatology in functional dyspepsia which should be investigated in future studies.